Modeling Religion's Impact on Urbanity - Rüpke, Jörg (History of religions, 2025)
How did the inherent ambivalence of religion impact the transformation of cities? This article starts from conceptualizing religion as being performed in three interrelated fields, namely communication, sacralization, and reflection. To explore how this practice of "religion" has changed and could change the interaction with human Others in urban contexts, I propose the notion of ambivalence, which has repeatedly, but never consistently, been employed for both the characterization of religion and the urban. To that purpose, the article analytically distinguishes the four dimensions of spatiality, temporality, materiality, and sociality. It proposes modeling religion within these four dimensions, situating religion in urban contexts, and exploring the impact of religion in each of the four dimensions with regard to a basic social ambivalence of the urban, namely its concurrent striving for unity, communality, and diversity. Methodologically, the aim is to develop a heuristic model for the investigation of the mutual formation of religion and urbanity based on observations taken from the history of religion. Complementing the other articles of this special issue, the argument is based on examples beyond South Asia and from the ancient Mediterranean in particular.